2022
DOI: 10.3390/nu14235073
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Alcohol Consumption with All-Cause Mortality, Hypertension, and Blood Pressure Change: Results from CHNS Cohort, 1993–2015

Abstract: Background: Previous studies have demonstrated a J-shaped association of alcohol consumption with all-cause mortality and hypertension, but the majority of these studies focus on a single measurement of alcohol intake and were conducted in a Western population. Whether long-term trajectories of alcohol consumption are associated with all-cause mortality, hypertension, and a change in blood pressure remains to be elucidated. Methods: In the large, population-based China Health and Nutrition Survey cohort from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…A recent cohort study conducted in China, which was not eligible for inclusion in the present meta-analysis because it lacked suitable data, provided no evidence for a smaller change of DBP in light or moderate drinkers, compared with nondrinkers, in a sex-adjusted multivariable model. 10 While we are not aware of systematic reviews or meta-analyses assessing the relationship between usual alcohol consumption at baseline and subsequent BP changes over time, 2 studies have investigated the association between alcohol intake and risk of hypertension, also focusing on possible sex-and region-specific effects. 27,28 The first review found a positive correlation between alcohol consumption and risk of hypertension in men, with no evidence of a threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent cohort study conducted in China, which was not eligible for inclusion in the present meta-analysis because it lacked suitable data, provided no evidence for a smaller change of DBP in light or moderate drinkers, compared with nondrinkers, in a sex-adjusted multivariable model. 10 While we are not aware of systematic reviews or meta-analyses assessing the relationship between usual alcohol consumption at baseline and subsequent BP changes over time, 2 studies have investigated the association between alcohol intake and risk of hypertension, also focusing on possible sex-and region-specific effects. 27,28 The first review found a positive correlation between alcohol consumption and risk of hypertension in men, with no evidence of a threshold.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort study conducted in China, which was not eligible for inclusion in the present meta-analysis because it lacked suitable data, provided no evidence for a smaller change of DBP in light or moderate drinkers, compared with nondrinkers, in a sex-adjusted multivariable model. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol intake was assessed by dietary intake using simple or standardized questionnaires, 24,27,28,[30][31][32][33]35,[37][38][39][40][41] interview-based questionnaire, 9,26,36 or interviews by trained and certified health professionals. 13,22,23 Four of the self-report studies used a food frequency questionnaire. 25,29,34,42 Details of the methods used for exposure assessment and calculation of alcohol dose are presented in the Table.…”
Section: Resultsmentioning
confidence: 99%
“…Urbanization index, daily total energy intake, and physical activity levels were calculated by the methods used in previous studies. 27,[41][42][43][44] The provinces were categorized into the northern regions (Liaoning, Heilongjiang, Shandong, and Henan) and southern regions (Jiangsu, Hubei, Hunan, Guangxi, and Guizhou) for further analysis, divided by the Qinling Mountain-Huaihe River Line. 45 The body mass index (BMI), a covariate added to the sensitivity analysis, was calculated by dividing weight (kg) by the square of height (m 2 ).…”
Section: Covariate Determinationmentioning
confidence: 99%